Impact of women under-representation in Nasarawa State House of Assembly, Nigeria - Kago, Malo Habila; Wan Mohd Nor, Murni; Ku Samsu, Ku Hasnita; Ismail, Mohd Mahadee (Human Resource Management Academic Research Society, 2023)
Political representation and participation involve forming political associations, voting, participating in decision-making, holding public office, and engaging in other political activities. The Inter-Parliamentary Union (IPU), with headquarters in Geneva, Switzerland, was founded in 1889 (Turner, B., 2011), promotes equal representation as a fundamental right of women that should be exercised under conditions of freedom, equity, transparency, and accountability, with due regard for the diversity of opinions and the polity's interests. However, in Nasarawa State, women were visibly absent in the parliament all through the four Nigerian republics (1963–1966, 1979–1983, 1992–1993, and 1999–date). This qualitative, in-depth study examines the impact of women’s under-representation in the Nasarawa State House of Assembly (NSHA) in the fourth Nigerian republic. A purposive sampling technique was used to select 13 females and 17 males who are experts in related fields of politics, and academia; for the study. There are three major findings: (i) the implications of the absence of women in the legislatures of the NSHA; (ii) the absence of socio-economic developmental policies in the NSHA, and (iii) insufficient information and candidate popularity among women and its implications for women's representation in the NSHA. The study is a novelty compared to previous research on the impact of women's under-representation in the NSHA because it is an in-depth exploration of the impact of women under-representation in one of the most badly affected states in Nigeria; specifically, in the NSHA.